Adolf Eichmann : executing the "Final Solution" - Streissguth, Thomas, 1958- (Holocaust heroes and Nazi criminals, 2005)
Presents a short history of Adolf Eichman, the Nazi SS officer charged with orchestrating the killing of millions of Jews during World War Two, and describes the efforts of Nazi hunters to locate him and bring him to trial.